Indecent exposure : a joint report on noise at work (RNID, 1999)
"A joint report by the TUC and the Royal National Institute for Deaf People reporting research which shows that many new industries expose their employees to damaging noise, and setting out an agenda for action by Government, employers and others. Case studies of individuals with noise induced hearing loss give a strong personal dimension to this problem ."